The Coming of Age of E-Prints in the Literature of Physics. - Cecelia M. Brown (Issues in Science and Technology Librarianship)
Examination of the role of e-prints in physics literature was conducted by citation analysis. Two databases were analyzed. Citation analysis was performed on e-prints from the Los Alamos e-print archive, arXiv.org, using the Stanford Public Information Retrieval System's High Energy Physics (SPIRES-HEP) and the Institute for Scientific Information's SciSearch databases. The SPIRES-HEP data represents citations to e-prints by e-prints while SciSearch data represents citations to e-prints by journal articles. Citations from 1991 to 1999 were examined. E-prints in the SPIRES-HEP database were cited approximately 10 times each by other e-prints, while those found in SciSearch were cited approximately 0.5 times each by journal articles. Despite this difference, the citation patterns were similar for both e-prints and journal articles. The citation rate by both e-prints and journals was highest from the high energy particle physics archives. The data from SPIRES-HEP indicates that e-prints are used to a greater extent by physicists than previously measured and that e-prints have become an integral and valid component of the literature of physics.